Translational formulation of microneedle drug delivery systems: challenges and active strategies - Vučen, Sonja (Archives of Pharmacy, 2022)
Microneedles are an emerging technology initially developed for minimally invasive cutaneous delivery of therapeutic molecules that were not capable of penetrating the skin. Their use quickly expanded to being used for other applications, such as ocular, gastrointestinal, mucosal, and buccal drug delivery, as well as sampling and sensing the skin interstitial fluid. In particular, dissolvable microneedles (DMN) offer an attractive delivery strategy for drugs and vaccines due to several advantages compared with solid or hollow microneedles. However, the translation of DMN from research laboratories to successful medicinal products is proved to be very challenging and demanding task due to several crucial factors that must be considered. This presentation will provide insight into these factors and an overview of materials and methods used for DMN fabrication along with their feasibility at industrial scale. In addition, safety and regulatory aspects for DMN as potential medicinal products will also be considered.